2002
DOI: 10.1074/jbc.m107400200
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the Phosphate-sensitive Elements in the Arrestin Family of Proteins

Abstract: Arrestins play a key role in the homologous desensitization of G protein-coupled receptors (GPCRs). These cytosolic proteins selectively bind to the agonist-activated and GPCR kinase-phosphorylated forms of the GPCR, precluding its further interaction with the G protein. Certain mutations in visual arrestin yield "constitutively active" proteins that bind with high affinity to the light-activated form of rhodopsin without requiring phosphorylation. The crystal structure of visual arrestin shows that these acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
202
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 130 publications
(211 citation statements)
references
References 32 publications
7
202
1
1
Order By: Relevance
“…The dominant positive arrestin3-(R170E) has previously been reported to bind to agonist-occupied receptors and mediate desensitization independent of receptor phosphorylation (10,33). When the arrestin3-(R170E) mutant and a phosphorylation insensitive delta opioid receptor were expressed, desensitization of the receptor was similar to the wild type (33).…”
Section: Discussionmentioning
confidence: 74%
“…The dominant positive arrestin3-(R170E) has previously been reported to bind to agonist-occupied receptors and mediate desensitization independent of receptor phosphorylation (10,33). When the arrestin3-(R170E) mutant and a phosphorylation insensitive delta opioid receptor were expressed, desensitization of the receptor was similar to the wild type (33).…”
Section: Discussionmentioning
confidence: 74%
“…Among the four vertebrate subtypes, arrestin-1 shows the highest receptor specificity and selectivity for P-Rh* (50). However, the mechanism of arrestin activation by GPCRs is conserved in all subtypes (17,18,53), suggesting that receptor binding induces similarly small domain movement in nonvisual arrestins, which leaves a large portion of the molecule essentially unchanged. This can explain why many nonreceptor signaling proteins bind comparably to free and GPCR-associated arrestins (53).…”
mentioning
confidence: 99%
“…Simultaneous engagement of both sensors, which only P-Rh* can achieve, triggers a global conformational change, allowing arrestin-1 transition to a high-affinity receptor-binding state. The activation mechanism appears to be conserved in nonvisual arrestins (17,18) that initiate a second round of signaling upon receptor binding. Thus, the arrestin-receptor complex serves as a nucleus of a signalosome (19), where the conformation of the receptor-bound arrestin apparently determines its interactions with multiple signaling proteins (20).…”
mentioning
confidence: 99%
“…11). Only the "phosphate sensor" in arrestin has been characterized extensively (6,8,9,(12)(13)(14)(15). It was shown that receptor-attached phosphates must break the salt bridge between Arg-175 and Asp-296 to destabilize the polar core and make high affinity arrestin binding possible (9).…”
mentioning
confidence: 99%